2003
DOI: 10.1046/j.1460-9592.2003.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Sensor Algorithms Expedite Pacemaker Follow‐ups

Abstract: Auto sensor adjustment required less time during routine PM clinical follow-up by reducing steps needed for manual sensor threshold adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Using the activity level of patients (more active, the same, or less active) they concluded that automatic adjustment is less time consuming than manual adjustment. This study supports the current trend in increasing automaticity in pacemakers, although it is disputable if such a rough guide as three levels of activity can be used as a guide for sensor optimization 13 . In general, sensor optimization methods are poorly described, mostly referring to the manufacturers advice.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Using the activity level of patients (more active, the same, or less active) they concluded that automatic adjustment is less time consuming than manual adjustment. This study supports the current trend in increasing automaticity in pacemakers, although it is disputable if such a rough guide as three levels of activity can be used as a guide for sensor optimization 13 . In general, sensor optimization methods are poorly described, mostly referring to the manufacturers advice.…”
Section: Discussionsupporting
confidence: 66%
“…To date, limited studies investigated the effect of sensor adjustment and to the best of our knowledge; our study is the first and largest randomized controlled study, comparing DSS with OSS in detail. Previous studies mainly compared different sensors and were not primarily designed to evaluate individual adjustment 5,8,13–16,20 . Sulke et al showed that appropriate programming of sensors is crucial in rate responsive pacing 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation